Estudo sobre a influência do massará no processo de formação de salitre em rebocos na região de Teresina - PI - Fernandes, Paulo Henrique Campos (2010)
This work had to verify the influence of massará, while mortar component, in the process of formation of saltpeter in cementitious plaster walls of buildings. The massará is a ceramic material, texture areno usually found in large volumes argillaceous sediments in Teresina, Piaui State capital, which is associated with the Portland cement mortar form for fixing and finishing in construction. Saltpeter or flowering is a pathology that happens in gypsum wallboard, which invariably reaction between soluble salts present in materials, water and oxygen. This pathology, supposedly credited to massará caused its use to suffer significant reduction in the market of the buildings. Verify this situation with particular scientific rigor is part of the proposal of this work. Grading tests Were performed, consistency limits (LL, LP and IP), determination of potential hydrogen, capacity Exchange (CTC), electrical conductivity (EC), x-ray fluorescence (FRX) and x-ray diffraction (DRX). Massará analysed samples in number six, including sample plastering salitrado presented potential hydrogen medium 5.7 in water and 5.2 on KCl n and electrical conductivity (EC), equal to zero. These results pointed to the affirmative that massará is a material that does not provide salinity content that can be taken into consideration. It is therefore concluded that the material analyzed not competing, at least with respect to the presence of soluble salts, for the formation of saltpeter